Interpretation of Oil Seepage of Source Rock Based Magnetic Survey in Cipari Cilacap District - Sukmaji Anom Raharjo; Sehah S (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
The magnetic survey had been conducted in Village of Cipari, District of Cipari, Region of  Cilacap to interpret to the location of the oil seepage source rock. Boundary of the research area is 108.75675°E – 108.77611°E and 7.42319°S – 7.43761°S. The observed total magnetic data is corrected and reducted to obtain the local magnetic anomaly data. The local magnetic anomaly data is applied to model the subsurface bodies anomalies based on the Mag2DC for Windows software. With be supported the geological information, the some bodies anomalies are interpreted as the basaltic igneous rock (c = 0.0051), the alternately of sandstone and claystone and insert of marl from Halang Formation (c = 0.0014), the breccia from Kumbang Formation (c = 0.0035), the alternately of sandstones and claystone with insert of marl and breccia from Halang Formation (c = 0.0036), the claystone from Tapak Formation (c = 0.0015), the alternately of sandstones and claystone with insert of marl and compacted breccia from Halang Formation (c = 0.0030), and the alternately of sandstone and claystone from   Halang Formation (c = 0.0020). The plantonic foraminifer fossils as resources of oil seepage are estimated in the sedimentaries rocks, where the oil flows from those rocks into the         reservoir (source rock). Based on the interpretation results, the source rock is above basaltic igneous rock with the approximate position is 108.76164°W and 7.43089°S; and the depth is 132.09 meters below the average topographic.